Training for Life and Healing: The Systemic Empowerment of Aboriginal and Torres Strait Islander Men and Women Through Vocational Education and Training. Issue 2 (December 2019) - Stephens, Anne; Monro, Davena
Abstract : This paper integrates the findings of two evaluations into the effectiveness of human health workforce training delivery and outcomes. In the period 2012–2015, Wontulp-Bi-Buya College ran the Certificate III in Addictions Management and Community Development and the Certificate IV in Indigenous Mental Health: Suicide Prevention. The key findings are presented under three thematic areas: personal to community wellbeing, enrolment and completion and withdrawal and employment and voluntary sector engagement. The outcomes of both evaluations are combined to build a picture of successful course delivery, satisfaction and completion rates that well exceed the national average. The significant contribution the authors draw from these is the problematisation and theorising of the concept of 'empowerment'. A term claimed by the College in its mission statement, the term 'systemic empowerment' has been co-developed with the College to both reclaim the concept of empowerment and to make sense of the personal and collective empowerment approach that serves as a framework for the trainer's pedagogy and course structures. Systemic empowerment contributes to the Colleges' theory of change to tackle very important contemporary social and political issues holistically and at their root and serves as an important model of adult vocational education and training for Aboriginal and Torres Strait Islander people